2021
DOI: 10.46743/2160-3715/2021.4918
|View full text |Cite
|
Sign up to set email alerts
|

Identity Transformation Through Substance Use Disorder Recovery: Introducing the Six Stage Model

Abstract: Narratives of substance use disorder recovery experience can provide useful qualitative conceptual categories and novel theories about the way in which recovery is experienced by individuals. This information can better inform definitions, concepts, and supports for recovery processes. The current study reviewed 30 written personal recovery biographies which were contained within student applications to the collegiate recovery program housed in the Center for Young Adult Addiction and Recovery at Kennesaw Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In line with previous research (Watkins et al, 2021), current review found that identity transformation played an important role in the process of recovery. Addiction "spoils" identities, and recovery involves "identity reverting" (re-engaging in roles and responsibilities individuals had prior to addiction), as well as establishing new roles (developing relationships, gaining employment and education; Reith & Dobbie, 2012).…”
Section: Maintenancesupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous research (Watkins et al, 2021), current review found that identity transformation played an important role in the process of recovery. Addiction "spoils" identities, and recovery involves "identity reverting" (re-engaging in roles and responsibilities individuals had prior to addiction), as well as establishing new roles (developing relationships, gaining employment and education; Reith & Dobbie, 2012).…”
Section: Maintenancesupporting
confidence: 89%
“…This had implications for self-perception (i.e., their sense of agency, control over gaming behaviour), how individuals made sense of their experiences, and recovery behaviours (i.e., choosing abstinence over reduced play time to stay well). Although the process of identity transformation is considered to be occurring organically in the course of recovery (Watkins et al, 2021), current findings suggest that participants may also consciously engage in it. At the stage of "Developing awareness" individuals actively considered the negative impact of excessive gaming on their identity compared to how they were like before becoming addicted (e.g., becoming reclusive, losing social skills).…”
Section: Maintenancementioning
confidence: 68%